2013
DOI: 10.1213/ane.0b013e31829847a1
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Effectiveness of Ramosetron for Preventing Postoperative Nausea and Vomiting

Abstract: Ramosetron has a significant effect for preventing PONV compared with a placebo, but less than that reported in previous analyses. Ramosetron also has statistically significant differences in preventing early and late POV compared with ondansetron, but the clinical significance may be questioned because the NNTs are large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
0
36
0
1
Order By: Relevance
“…Post-operative nausea and vomiting are the common problems in patients undergoing surgical procedures [10,[13][14][15]. Risk of acid aspiration is another concern in patients undergoing surgery under general anesthesia [16].…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative nausea and vomiting are the common problems in patients undergoing surgical procedures [10,[13][14][15]. Risk of acid aspiration is another concern in patients undergoing surgery under general anesthesia [16].…”
Section: Discussionmentioning
confidence: 99%
“…6 A meta-analysis shows that ramosetron is superior to ondansetron for preventing PONV. 7 PONV are common phenomenon after laparoscopic cholecystectomy, with a reported incidence from 53% to 72%. 8,9 Because of the multifactorial etiology of PONV and its occurrence associated with anaesthetic techniques, there has been an increasing interest in using prophylactic antiemetic and anaesthesia with intravenous anaesthetic agents like propofol, with known antiemetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…37 Our study showed that palonosetron was no different than ondansetron in the rates of headache, dizziness, or drowsiness. Previous meta-analyses showed that other 5-HT 3 RAs, including ondansetron, granisetron, and ramosetron, had similar rates of adverse effects when used for the prevention of PONV, 10,38 and use of palonosetron did not result in a higher incidence of adverse effects compared with other 5-HT 3 RAs for the prevention of chemotherapy-induced nausea and vomiting. 18,19 Nevertheless, we cannot easily draw a conclusion regarding the safety profile of palonosetron because the studies in this meta-analysis did not report the incidence of all common adverse effects or any rare but severe adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Méthodes Nous avons effectué une recherche systématique dans les bases de données MEDLINE Ò , EMBASE TM , le Registre central Cochrane des essais cliniques contrô lés et Web of Science Ò pour identifier les essais randomisés contrô lés qui ont abordé la comparaison de l'efficacité antiémétique dans les 24 premières heures suivant une chirurgie, du palonosétron et de l'ondansétron administrés à titre prophylactique. Les principaux critères d'évaluation étaient le pourcentage de participants éprouvant des nausées postopératoires (NPO), des vomissements postopératoires (VPO) ou les deux, dans la période précoce (0-6 heures) ou tardive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Postoperative nausea and vomiting (PONV), the big ''little problem'', 1 is the most common postoperative medical problem. From the perspective of both patients and healthcare providers, prophylaxis of PONV is equally as important as postoperative analgesia.…”
Section: Résuméunclassified
See 1 more Smart Citation